Wodaabe - Herdsmen of the Sun - Herzog, Werner; Schmidt-Reitwein, Jörg (Werner Herzog: Documentaries and Shorts, 2006)
From the camera of the sometimes obsessive, always provoking director Werner Herzog comes this documentary of the Wodaabe people of the Sahara/Sahel region. In focusing on the tribe's spectacular courtship rituals and "beauty pageants", where eligible young men strive to outshine each other and attract mates by means of lavish makeup, posing, and facial movements, "Herdsmen" gives insight into the politics of gender with global resonance - all governed by the director's penchant for excess. [www.kino.com]